Team production in competitive labor markets with adverse selection - Siemens, Ferdinand von 1973-; Kosfeld, Michael 1969- (CESifo working paper, 2014)
Team production is a frequent feature of modern organizations. Combined with team incentives, team production can create externalities among workers, since their utility upon accepting a contract depends on their team's performance and therefore on their colleagues' productivity. We study the effects of such externalities in a competitive labor market if workers have private information on their productivity. We find that in any competitive equilibrium there must be Pareto-efficient separation of workers according to their productivity. We further find that externalities facilitate equilibrium existence, where under a particular condition on workers' indifference curves even arbitrarily small externalities guarantee equilibrium existence